2018
DOI: 10.1038/s41438-018-0029-y
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species and nitric oxide induce senescence of rudimentary leaves and the expression profiles of the related genes in Litchi chinensis

Abstract: Litchi is one of the most important subtropical evergreen fruit trees in southern Asia. Previous studies indicated that high-temperature conditions encourage growth of rudimentary leaves in panicles and suppress flowering. We have demonstrated that methyl viologen dichloride hydrate (MV) and sodium nitroprusside (SNP) promoted flowering in litchi partially by inhibiting the growth of rudimentary leaves via reactive oxygen species (ROS) and nitric oxide (NO). In the present study, we examined the microstructure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…PA catabolism by amine oxidases, copper-containing amine oxidases (CuAOs), flavin-containing PA oxidases (PAOs) and the parallel production of H 2 O 2 can result in two different scenarios. High H 2 O 2 levels lead to programmed cell death (PCD) [72], while low H 2 O 2 level is efficiently scavenged by enzymatic/nonenzymatic antioxidant factors that help plants to survive abiotic stress, using different defense mechanisms [73]. In the present study, ROS related genes such as peroxisome 1 (PEX1), isocitrate dehydrogenase, COPPER/ZINC SUPEROXIDE DISMUTASE, FLAVANONE 3-HYDROXYLASE, Peroxidase, HXXXD-type acyl-transferase family protein as well as many stress-related genes (Disease resistance protein, Glycosyl hydrolase, Cysteine-rich secretory proteins, Serine/threonine-protein kinase MAPK/ERK KINASE 4, VASCULAR ASSOCIATED DEATH1, Leucine-rich repeat protein kinase, Riboflavin synthase-like superfamily protein and Pentatricopeptide repeat) were found down-regulated in June "OFF" inflorescence buds vs June "ON" inflorescence buds.…”
Section: Discussionmentioning
confidence: 99%
“…PA catabolism by amine oxidases, copper-containing amine oxidases (CuAOs), flavin-containing PA oxidases (PAOs) and the parallel production of H 2 O 2 can result in two different scenarios. High H 2 O 2 levels lead to programmed cell death (PCD) [72], while low H 2 O 2 level is efficiently scavenged by enzymatic/nonenzymatic antioxidant factors that help plants to survive abiotic stress, using different defense mechanisms [73]. In the present study, ROS related genes such as peroxisome 1 (PEX1), isocitrate dehydrogenase, COPPER/ZINC SUPEROXIDE DISMUTASE, FLAVANONE 3-HYDROXYLASE, Peroxidase, HXXXD-type acyl-transferase family protein as well as many stress-related genes (Disease resistance protein, Glycosyl hydrolase, Cysteine-rich secretory proteins, Serine/threonine-protein kinase MAPK/ERK KINASE 4, VASCULAR ASSOCIATED DEATH1, Leucine-rich repeat protein kinase, Riboflavin synthase-like superfamily protein and Pentatricopeptide repeat) were found down-regulated in June "OFF" inflorescence buds vs June "ON" inflorescence buds.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al [183] have elucidated senescence-inducing ROS-NO crosstalk in litchi plants and have described the morphological, structural, PCD, and expression characteristics of senescence genes after treatment with ROS and NO. Their results show the distorted structure and morphology as well as the upregulation of LcRBOH, LcMC-1-like and LcPirin genes, which play a role in ROS-and NO-mediated senescence and leaf abscission in litchi plants [183]. NO and ROS have also been reported to play a vital role in signaling cascades and defense mechanisms in legumes and rhizobia [184].…”
Section: No and Crosstalk With Other Plant Growth Regulatorsmentioning
confidence: 99%
“…We have previously focused on the feature of the low temperature-, ROS-, and NO-induced senescence of panicle leaves, and found that programmed cell death (PCD) is involved in the panicle leaf growth regulation by ROS and NO, as well as by low temperature in litchi [6, 8]. We also screened PCD related genes from our RNA-seq data sets of the ROS-treated rudimentary leaves [9], and identified a litchi homolog MCII ( LcMCII-1 ).…”
Section: Introductionmentioning
confidence: 99%